2019
DOI: 10.1016/j.jvs.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preoperative cognitive impairment and type of vascular surgery procedure on postoperative delirium with associated cost implications

Abstract: POD is predicted by type of vascular surgery procedure, impaired cognition (MoCA), and previous delirium. Costs and morbidity related to delirium are greatest for those with impaired cognitive burden. Preoperative MoCA screening can identify those at highest risk, allowing procedure modification and informed care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…Delirium is a concern in the elderly; evidence suggests increased risk only in MOCA of less than 15; this patient has MOCA of 23. 17 Age of more than 70 years correlates with only a small increase in major perioperative complications (7.5% vs 4.8%). 18 The EUROSTAR study demonstrated that EVAR patients return to preoperative status sooner.…”
Section: Discussionmentioning
confidence: 93%
“…Delirium is a concern in the elderly; evidence suggests increased risk only in MOCA of less than 15; this patient has MOCA of 23. 17 Age of more than 70 years correlates with only a small increase in major perioperative complications (7.5% vs 4.8%). 18 The EUROSTAR study demonstrated that EVAR patients return to preoperative status sooner.…”
Section: Discussionmentioning
confidence: 93%
“…As patients with pre-existing cognitive impairment are more likely to develop postoperative delirium (Styra et al, 2019), it will be important to determine whether microglia in neurodegenerative disorders are amenable to peri-operative manipulations that prevent its activation and the onset of postoperative delirium.…”
Section: Potential Developments In the Fieldmentioning
confidence: 99%
“…Delirium is a neuropsychiatric disorder that is characterized by acute and fluctuating changes in baseline attention, awareness, and cognition 1 . Postoperative delirium (POD) is defined by a disturbance of consciousness that is accompanied by impaired attention or inability to focus that cannot be explained by a pre-existing or evolving neurocognitive disorder 1 , 2 . POD is well known to be associated with prolonged hospital stay and medical morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…POD is well known to be associated with prolonged hospital stay and medical morbidities. It also increases medical costs 2 4 .…”
Section: Introductionmentioning
confidence: 99%